Value for money and adaptive programming - Approaches, measures and management - Laws, Ed; Valters, Craig (ODI, 2021)
- The United Kingdom’s Foreign, Commonwealth and Development Office (FCDO)’s standard economy, efficiency, effectiveness/cost-effectiveness and equity (4E) framework is still relevant for approaching, measuring and managing value for money (VfM) for adaptive programmes. • However, this framework needs to be reframed to capture and incentivise flexibility, learning and adaptation. • VfM appraisal and reporting should be done in a way that draws on beneficiary feedback and informs good decision-making, rather than just being a compliance exercise. • If VfM appraisal and reporting cannot be done appropriately for adaptive programmes, it should be avoided or minimised. There is a risk of diverting time and resources from more suitable tools and methods.

Lessons learned from PERL and partners' response to the COVID-19 crisis - Sharp, Samuel; Nwachukwu, Tochukwu; Srivatsa, Sripriya Iyengar (PERL Programme, 2021)
The first case of COVID-19 in Nigeria was confirmed on 27 February 2020, with the first lockdown orders issued on 30 March 2020. The pandemic and resultant containment measures have had farreaching socio-cultural, economic, financial and political implications, globally as well as in Nigeria. For the Partnership to Engage, Reform and Learn (PERL) and its partners, the pandemic has required considerable adaptation of their strategic approach and working practices. This report reflects on how COVID-19 changed the operating context for PERL’s partners, how PERL responded and what lessons have been learned across delivery teams. For government partners, the most substantial impacts have been to budgets, struck by falling oil prices and reduced economic activity. Universally, states have had to adjust budgets and reforecast, revising budgets downwards and shifting the focus of expenditure towards healthcare. The World Bank’s State Fiscal Transparency, Accountability and Sustainability (SFTAS) Programme has generated powerful incentives for this budget revision, which PERL has been able to work alongside. A range of new governance structures – such as public response committees and task forces – have been established to deal with various aspects of COVID-19 policy, and PERL has had to grapple to maintain its ongoing engagement with these. For civil society organisations (CSOs), the closure of offices from 30 March 2020 has changed the nature of engagement with government. CSOs often developed innovative approaches to maintaining access, including use of social media and direct calls. But the shift to virtual working has been challenging for many CSOs, both in terms of covering the costs of data for virtual meetings and the risks of disengagement and marginalisation for some organisations. In response to this changed context, from March 2020 PERL began to restrategise. The flexible nature of the programme’s workplans, progress markers and budgets enabled activities to be adjusted in a relatively timely manner, with a new workplan approved by the end of April 2020. Central PERL management developed a COVID-19 response strategy which provided a broad framework for adaptations, but allowed substantial autonomy to state and regional teams to lead on reprioritisation according to their understanding of the local context. This was valued by both management and delivery staff. Challenges manifested themselves more in effectively delivering on these adapted workplans than in the process of restrategising – due to two rounds of budget cuts, the merger of DFID and the FCO to form the Foreign, Commonwealth and Development Office (FCDO) and the difficulties of engaging partners virtually. Overall, the pandemic undoubtedly delayed activities (by roughly three months for deprioritised areas of work), but resulted in an array of new, tailored interventions under its broad categories of work. Interventions relating to the health sector became more prevalent, as did work supporting budget adjustments. Domestic resource mobilisation and education interventions were often adjusted to be more relevant to the COVID context or experienced delay. The report provides short illustrative case studies of PERL’s adaptations to: support budget revisions; work with media partners on COVID-19 sensitisation; tracking and advocacy for palliative distribution; and support for the introduction of tax relief. There is some evidence, albeit partial, that PERL was able to take advantage of windows of opportunity offered by the pandemic to drive ahead with certain ongoing reform initiatives.

Pushing boundaries: Advocacy evaluation and real-time learning in an HIV prevention research advocacy coalition in sub-Saharan Africa - Dasmariñas, Jules; Schlangen, Rhonda (New Directions for Evaluation, 2021)
Evaluation processes that facilitate learning among advocates must be nimble, creative, and meaningful while transcending putative performance and accountability management. This article describes the experience, lessons, and trajectory of one such approach, Simple, Participatory Assessment of Real Change (SPARC), that a transnational HIV prevention research advocacy coalition pilot-tested in sub-Saharan Africa. Inspired by the pioneering work of the outcome harvesting (OH) and participatory evaluation community, we recuperate advocates' centrality as storytellers, sense-makers, and strategists in advocacy evaluation and describe how we recalibrated SPARC to meet their evaluation and learning needs. This article highlights the normative value of deliberative discourse in evaluation as it contributes to the interpretation of OH and the enrichment of the theory and practice of advocacy evaluation.